Historical Analysis of Dutch Education Policy Towards Indigenous Peoples - Cici Adiputri; Najuah; Cindy Via Situngkir; Safwani Daulay; Wardah (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study discusses the historical analysis of Dutch educational policies towards indigenous people in the Dutch East Indies. The objectives of this study are to determine the form of Dutch colonial educational policies, understand the objectives of implementing an education system for indigenous people, and analyze the impact of these policies on social development and nationalism in Indonesia. The research method used is a historical research method with a qualitative approach through literature study. Data were obtained from various sources such as books, journals, historical documents, and research results relevant to the topic of study. The results show that Dutch colonial education was initially discriminatory and only intended for certain groups, such as European children, nobles, and families of indigenous officials. Education was used as a political tool to support administrative interests and maintain colonial power in the Dutch East Indies. Policy changes began to be seen with the implementation of the Ethical Policy in the early 20th century through educational programs that opened wider educational opportunities for indigenous people. However, the main objective of colonial education remained directed at creating an educated workforce at a low cost and loyal to the Dutch government. On the other hand, the development of colonial education had a significant impact on the emergence of an educated indigenous class with a national consciousness. Western-educated intellectuals began to understand the concepts of freedom, democracy, and nationalism, which then led to the emergence of national movement organizations in Indonesia. Figures such as Ki Hajar Dewantara, Mohammad Hatta, and Soetomo utilized education as a means of fighting against colonialism. Thus, Dutch education policy had a dual impact: it served as both a tool of colonial power and a factor in the growth of Indonesian nationalism.